Environmental Safety of Design and Construction of Commercial and Residential Buildings - I., Kushnazarov P. (European Journal of Life Safety and Stability (2660-9630), 2021)
This article attempts to briefly discuss environmental issues in the construction industry. Energy use in the modern world has become a serious environmental problem as buildings consume a significant percentage of electrical energy. Each stage of construction requires energy, including design, construction and demolition. One way to solve this energy problem is to use energy efficiently in our buildings and industrial facilities. Ideally, our homes should be built using a percentage of the current energy requirements of such buildings. This will significantly reduce the rate of depletion of our non-renewable energy resources such as oil and coal. In addition, there will be a reduction in greenhouse gas emissions from buildings.